Comparison of laboratory and field testing performance evaluations of siloxane-polyurethane fouling-release marine coatings. Issue 8 (13th September 2016) - Stafslien, Shane J.; Sommer, Stacy; Webster, Dean C.; Bodkhe, Rajan; Pieper, Robert; Daniels, Justin; Vander Wal, Lyndsi; Callow, Maureen C.; Callow, James A.; Ralston, Emily; Swain, Geoff; Brewer, Lenora; et al.
Abstract: A series of eight novel siloxane-polyurethane fouling-release (FR) coatings were assessed for their FR performance in both the laboratory and in the field. Laboratory analysis included adhesion assessments of bacteria, microalgae, macroalgal spores, adult barnacles and pseudobarnacles using high-throughput screening techniques, while field evaluations were conducted in accordance with standardized testing methods at three different ocean testing sites over the course of six-months exposure. The data collected were subjected to statistical analysis in order to identify potential correlations. In general, there was good agreement between the laboratory screening assays and the field assessments, with both regimes clearly distinguishing the siloxane-polyurethane compositions comprising monofunctional poly(dimethyl siloxane) (PDMS) (m-PDMS) as possessing superior, broad-spectrum FR properties compared to those prepared with difunctional PDMS (d-PDMS). Of the seven laboratory screening techniques, the Cellulophaga lytica biofilm retraction and reattached barnacle ( Amphibalanus amphitrite ) adhesion assays were shown to be the most predictive of broad-spectrum field performance.